RATIO OF EDUCATION DEVELOPMENT INDEX AND EXPENDITURES PER STUDENT-YEAR: SOME APPROXIMATIONS OF CORRELATIONS AND THEIR RELEVANCE TO IMPROVE INVESTMENTS IN EDUCATION - Oliveira, Rejane de [UNESP]; Lemes, Sebastiao de Souza [UNESP] (Unesp-faculdade Ciencias & Letras, 2016)
This study presents the behavior of the Education Development Index in two regions in Sao Paulo State, correlated with the spending per student a year as a proportion of the municipal GDP per capita during the years, after joining the Target Plan Everyone for Education Commitment. The general aim was to analyze and discuss the relation between spending per student a year in the initial grades of basic education and the development of the municipal education quality represented by EDIB quality indicator as evidence of commitment and responsibility to the quality of education. This is a quantitative study, which used statistical methods for analysis of the variables. There is an evident correlation between the EDIB variables and spending per student a year, as a proportion of GDP per capita for municipalities in a region that has not accomplished their goals, and there is also a strong correlation to the second region as a whole.
Keywords: EDIB; EDP; Student a Year Spending Quality; Articulated Action Plan; Target Plan Everyone for Education Commitment